Spatial patterns of access to retail food outlets in Mexico city - González-Alejo,Ana Laura (2019)
Trade liberalization in Mexico from 1980 extended the domain of forms of modern supply, as well as stagnating modalities of traditional supply; however, the uneven growth of these supply forms has generated territorial inequalities. This article aims to identify patterns of access to food retail and its association with urban marginalization in Mexico City from a spatial perspective. In the first part, a conceptual revision of the food deserts is presented as an approach through which territorial disparities are recognized in relation to, not only physical access, but also economic limitations that make it impossible for people to move to centres of consumption, restricting them to spaces within their proximity. In the second part, particularities are scrutinized, regarding the urban structure of Mexico City, which influence the differentiated distribution of the types of food supply. Subsequently, a methodological strategy is presented for the delimitation of areas with differentiated proximity to points of sale of fresh and processed foods from a mobile focal reference point, applied in territories with different levels of urban marginalization. Finally, the patterns of access to retail food establishments are revealed. These manifest themselves as large areas of the centre, north and east of the city, exposed to an unhealthy food environment, while the peripheral areas of the west, south and southeast are under the influence of food deserts.